HUBUNGAN DISIPLIN DENGAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENGOLAHAN MAKANAN INDONESIA 1 DI SMK NEGERI 9 PADANG - ariefiani, mega nita; baidar, baidar; elida, elida (Journal of Home Economics and Tourism, 2013)
This study aimed to determine the relationship of the discipline to the student learningoutcomes in subjects Indonesia Food Processing 1 in State 9 Padang Vocational High School.Covering aspects of punctuality, obedience and responsibility in teaching students both theoryand practice. This study is correlational. The population in this study were all students of class XFood Services State 9 Padang Vocational High School , the sample in this study amounted to 64people with a proportionate random sampling technicians. The data analysis technique used isthe correlation product moment correlation formula. Results showed that students who attendschool in State 9 Padang Vocational High School, generally belonging to the category of beingdisciplined, while students' largely belong to the category not pass / fail. Disciplines studying therelationships between variables (X) with the learning outcomes Indonesia Food Processing 1 (Y),has a positive and significant relationship with a correlation of 0.827, correlation coefficientsignificance test results tcount> T (11.577> 1.671).Keyword: Discipline is positively associated with student learning outcomes. table